Self-cleaning ceramic tile coating as well as preparation method and application thereof

By modifying the unmodified wax emulsion with non-ionic emulsifier and auxiliaries, and combining self-crosslinking emulsion and silane coupling agent, a heterogeneous system is formed, which solves the problems of poor adhesion, water resistance, stain resistance, scratch resistance and recoating performance of existing ceramic tile coatings, and achieves self-cleaning ceramic tile coatings with high adhesion and good performance.

CN120005461APending Publication Date: 2025-05-16SHENZHEN GRANDLAND ENVIRONMENTAL COATING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510278129.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-05-16

AI Technical Summary

Technical Problem

Existing ceramic tile coatings have poor adhesion, poor water resistance, poor stain resistance, poor scratch resistance and poor recoating performance on the surface of ceramic tile, making it difficult to meet the application needs of kitchen and bathroom tiles.

Method used

The unmodified wax emulsion is modified by non-ionic emulsifiers and a supplementary emulsifiers, and combined with self-crosslinking emulsions and silane coupling agents to form a heterogeneous system to improve the adhesion, hydrophobicity, scratch resistance and recoating properties of the coating.

Benefits of technology

It achieves good adhesion of the paint on the tiles, has good hydrophobicity, water resistance, scratch resistance and recoating performance, and meets the application needs of kitchen and bathroom tiles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005304845400000141
    Figure BDA0005304845400000141
  • Figure BDA0005304845400000142
    Figure BDA0005304845400000142
  • Figure BDA0005304845400000151
    Figure BDA0005304845400000151
Patent Text Reader

Abstract

The invention belongs to the field of building materials, and particularly relates to a self-cleaning ceramic tile coating as well as a preparation method and application thereof. The self-cleaning ceramic tile coating is prepared from 8.0 wt% to 30.0 wt% of water, 0.1 wt% to 0.6 wt% of cellulose, 0.1 wt% to 1.0 wt% of pH multifunctional auxiliaries, 5.0 wt% to 20.0 wt% of titanium dioxide, 3.0 wt% to 10.0 wt% of inorganic filler, 30.0 wt% to 60.0 wt% of self-crosslinking emulsion, 1.0 wt% to 10.0 wt% of modified wax emulsion, 2.0 wt% to 6.0 wt% of coalescing agents, 1.0 wt% to 5.0 wt% of silane coupling agents and 0.1 wt% to 5.6 wt% of auxiliaries. The modified wax emulsion is obtained by carrying out a modification reaction on an unmodified wax emulsion by adopting a nonionic emulsifier and a co-emulsifier. The key of the invention lies in that the specific multiphase system modified wax emulsion is introduced, and on the basis, the modified wax emulsion is matched with the self-crosslinking emulsion and the silane coupling agent, so that the obtained self-cleaning ceramic tile coating has good hydrophobicity, water resistance and recoatability and relatively high adhesive force and scratch resistance; the application requirements of kitchen and bath ceramic tiles can be well met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building materials, and in particular relates to a self-cleaning tile coating and a preparation method and application thereof. Background Art

[0002] According to a survey, most of the traditional old houses’ kitchens and bathrooms are paved with absorbent bricks. Although the cost of paving with absorbent bricks is low, absorbent bricks have a strong ability to absorb stains. Stains that have been stained for a long time may not be cleaned off, making them difficult to clean. In addition, the surface of the tiles is prone to watermarks and leakage marks after long-term water absorption, reducing the aesthetics of the interior. At the same time, absorbent bricks have poor wear resistance. In daily use, the surface is easily scratched due to friction, reducing its service life.

[0003] With the rapid development of the real estate and construction industries, urban building construction is changing with each passing day. People's aesthetic concepts for buildings and house decoration are constantly improving. More and more consumers are beginning to pay attention to the renovation of kitchen and bathroom tiles in old houses. Compared with the traditional practice of removing old tiles and re-laying new tiles, the use of paint renovation is more time-saving, labor-saving and cost-saving, and achieves practical and beautiful effects. Conventional interior wall paints use water as the dispersion medium, water-based resin as the film-forming substance, and are made of auxiliary materials such as pigments, fillers, and additives. They have excellent properties such as safety, ecology, non-toxicity, and pollution-free, and are in line with the healthy and environmentally friendly concept advocated by modern society. However, on the smooth surface of tiles, there are defects such as poor adhesion, poor water resistance, poor stain resistance, poor scratch resistance, and poor recoating. Summary of the invention

[0004] The inventors of the present invention have found through extensive and in-depth research that the prior art often uses a method of adding silane coupling agents to improve the adhesion of coatings on tiles, but this also causes the hydrophobicity and recoating performance of the coating to deteriorate, making it difficult to meet the application requirements of kitchen and bathroom tiles. Therefore, in view of the problems existing in existing tile coatings, the inventors of the present invention creatively propose to modify the unmodified wax emulsion using a nonionic emulsifier and an auxiliary emulsifier, and the obtained modified wax emulsion cooperates with a self-crosslinking emulsion, a silane coupling agent and other auxiliary components to improve the adhesion of the coating while giving the coating good hydrophobicity, recoating performance and scratch resistance.

[0005] One of the objects of the present invention is to provide a self-cleaning tile coating.

[0006] The second object of the present invention is to provide a method for preparing the self-cleaning tile coating.

[0007] The third object of the present invention is to provide the application of the self-cleaning tile coating in kitchen and bathroom tiles and other building materials.

[0008] Specifically, based on the total weight of the self-cleaning tile coating, the self-cleaning tile coating contains 8.0-30.0wt% of water, 0.1-0.6wt% of cellulose, 0.1-1.0wt% of pH multifunctional additive, 5.0-20.0wt% of titanium dioxide, 3.0-10.0wt% of inorganic filler, 30.0-60.0wt% of self-crosslinking emulsion, 1.0-10.0wt% of modified wax emulsion, 2.0-6.0wt% of film-forming additive, 1.0-5.0wt% of silane coupling agent, and 0.1-5.6wt% of additive; the modified wax emulsion is obtained by modifying the unmodified wax emulsion with a non-ionic emulsifier and an emulsifier.

[0009] In a preferred embodiment, the mass ratio of the unmodified wax emulsion to the nonionic emulsifier and the co-emulsifier is 1:(0.02-0.04):(0.03-0.06).

[0010] In a preferred embodiment, the unmodified wax emulsion is selected from at least one of polyethylene wax emulsion, carnauba wax emulsion, silica wax emulsion and polypropylene wax emulsion.

[0011] In a preferred embodiment, the nonionic emulsifier is selected from at least one of sorbitan fatty acid ester emulsifiers, polyoxyethylene sorbitan fatty acid ester emulsifiers, and fatty alcohol polyoxyethylene ether emulsifiers.

[0012] In a preferred embodiment, the co-emulsifier is selected from at least one of polyglycerol esters, glycerol, and stearic acid.

[0013] In a preferred embodiment, the modification reaction conditions include: temperature of 150-180° C. and time of 6-10 h.

[0014] In a preferred embodiment, the particle size of the modified wax emulsion is 0.1-1 μm.

[0015] In a preferred embodiment, the particle size of the self-crosslinking emulsion is 0.05-0.1 μm.

[0016] In a preferred embodiment, the self-crosslinking emulsion is an acrylic self-crosslinking emulsion.

[0017] In a preferred embodiment, the silane coupling agent is selected from aminosilane and epoxysilane.

[0018] In a preferred embodiment, the mass ratio of the aminosilane to the epoxysilane is 1:(1-3).

[0019] In a preferred embodiment, the cellulose is selected from at least one of carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose.

[0020] In a preferred embodiment, the inorganic filler is selected from at least one of heavy calcium carbonate, barium sulfate, kaolin, talc, diatomaceous earth, mica powder, and calcium silicate powder.

[0021] In a preferred embodiment, the film-forming aid is selected from at least one of alcohol ester dodecahydrate, alcohol ester hexahydrate, OE300, and OE400.

[0022] In a preferred embodiment, the auxiliary agent is selected from at least one of a defoamer, a dispersant, a wetting agent, a preservative, a thickener, and an anti-mildew and anti-algae agent.

[0023] In a preferred embodiment, based on the total weight of the self-cleaning tile coating, the content of the defoamer is 0.2-0.8wt%, the content of the dispersant is 0.3-1.0wt%, the content of the wetting agent is 0.1-1.0wt%, the content of the preservative is 0.1-1.0wt%, the content of the thickener is 0.1-0.8wt%, and the content of the mildew and algae preventer is 0.2-1.0wt%.

[0024] The preparation method of the self-cleaning tile coating comprises: mixing water, cellulose, pH multifunctional additive, titanium dioxide, inorganic filler, self-crosslinking emulsion, modified wax emulsion, film-forming additive, silane coupling agent and additives to obtain the self-cleaning tile coating.

[0025] The key of the present invention is to introduce a wax emulsion modified by a specific multiphase system, and on this basis, the modified wax emulsion cooperates with a self-crosslinking emulsion and a silane coupling agent, which can not only give the coating system good hydrophobicity, but also a contact angle of up to 140°, making it difficult for water droplets to come into contact with the surface of the coating or to hang on the coating, having a good self-cleaning effect and being beneficial to improving water resistance, and the particles in the wax emulsion cooperate with the particles in the self-crosslinking emulsion, making the coating system more stable, being beneficial to improving the compactness of the coating, improving the scratch resistance and water resistance of the coating, and also improving the recoating performance, while the self-crosslinking emulsion cooperates with the silane coupling agent to give the coating significantly improved adhesion. In summary, the self-cleaning tile coating provided by the present invention has good hydrophobicity, water resistance, recoating performance, as well as high adhesion and scratch resistance, and can well meet the application requirements of kitchen and bathroom tiles. DETAILED DESCRIPTION

[0026] The self-cleaning tile coating provided by the present invention contains water, cellulose, pH multifunctional additive, titanium dioxide, inorganic filler, self-crosslinking emulsion, modified wax emulsion, film-forming additive, silane coupling agent, and additives. Based on the total weight of the self-cleaning tile coating, the water content is 8.0-30.0wt%, such as 8.0wt%, 10.0wt%, 1.0wt%, 15.0wt%, 18.0wt%, 20.0wt%, 22.0wt%, 25.0wt%, 28.0wt%, 30.0wt% or any value therebetween; the cellulose content is 0.1-0.6wt%, such as 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt% or any value therebetween; the pH multifunctional additive is 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt% or any value therebetween; The content of the agent is 0.1-1.0wt%, such as 0.1wt%, 0.2wt%, 0.5wt%, 0.8wt%, 1.0wt% or any value therebetween; the content of the titanium dioxide is 5.0-20.0wt%, such as 5.0wt%, 8.0wt%, 10.0wt%, 12.0wt%, 15.0wt%, 18.0wt%, 20.0wt% or any value therebetween; the content of the inorganic filler is 3.0-10.0wt%, such as 3.0wt%, 5.0wt%, 8.0wt%, 10.0wt% or any value therebetween The content of the self-crosslinking emulsion is 30.0-60.0wt%, such as 30.0wt%, 35.0wt%, 40.0wt%, 45.0wt%, 50.0wt%, 55.0wt%, 60.0wt% or any value therebetween; the content of the modified wax emulsion is 1.0-10.0wt%, such as 1.0wt%, 2.0wt%, 5.0wt%, 8.0wt%, 10.0wt% or any value therebetween; the content of the film-forming aid is 2.0-6.0wt%, such as 2.0wt%, 3.0wt%, 4.0wt% , 5.0wt%, 6.0wt% or any value therebetween; the content of the silane coupling agent is 1.0-5.0wt%, such as 1.0wt%, 2.0wt%, 3.0wt%, 4.0wt%, 5.0wt% or any value therebetween; the content of the auxiliary agent is 0.1-5.6wt%, such as 0.1wt%, 0.2wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.5wt%, 2.0wt%, 3.0wt%, 4.0wt%, 5.0wt%, 5.6wt% or any value therebetween.

[0027] Furthermore, based on the total weight of the self-cleaning tile coating, the water content is preferably 15.0-30.0wt%, such as 15.0wt%, 18.0wt%, 20.0wt%, 22.0wt%, 25.0wt%, 28.0wt%, 30.0wt% or any value therebetween; the cellulose content is preferably 0.1-0.5wt%, such as 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt% or any value therebetween; the pH multifunctional additive content is preferably 0.1-0.5wt%, such as 0.1wt%, 0.2wt%, 0.3wt%. 0.4wt%, 0.5wt% or any value therebetween; the content of the titanium dioxide is preferably 8.0-18.0wt%, such as 8.0wt%, 10.0wt%, 12.0wt%, 15.0wt%, 18.0wt% or any value therebetween; the content of the inorganic filler is preferably 3.0-8.0wt%, such as 3.0wt%, 4.0wt%, 5.0wt%, 6.0wt%, 7.0wt%, 8.0wt% or any value therebetween; the content of the self-crosslinking emulsion is preferably 40.0-60.0wt%, such as 40.0wt%, 42wt%, 45.0wt%, 48wt%, 50.0wt%, 52wt%, 55.0wt%, 58wt%, 60.0wt% or any value therebetween; the content of the modified wax emulsion is preferably 3.0 % , such as 3.0wt%, 5.0wt%, 8.0wt%, 10.0wt% or any value therebetween; the content of the film-forming aid is preferably 3.0-6.0wt%, such as 3.0wt%, 4.0wt%, 5.0wt%, 6.0wt% or any value therebetween; the content of the silane coupling agent is preferably 1.0-4.0wt%, such as 1.0wt%, 2.0wt%, 3.0wt%, 4.0wt% or any value therebetween; the content of the auxiliary agent is preferably 0.1-3.8wt%, such as 0.1wt%, 0.2wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 3.8wt% or any value therebetween.

[0028] In the present invention, the modified wax emulsion is obtained by modifying the unmodified wax emulsion with a nonionic emulsifier and an auxiliary emulsifier. The modified wax emulsion obtained by modifying with a specific multiphase system can improve the hydrophobicity of the coating system, and cooperate with the self-crosslinking emulsion and the silane coupling agent to improve the adhesion and scratch resistance of the coating film and improve the recoating performance.

[0029] Furthermore, the mass ratio of the unmodified wax emulsion to the nonionic emulsifier and the co-emulsifier is preferably 1:(0.02-0.04):(0.03-0.06). Based on the mass of the unmodified wax emulsion as 1 part by weight, the amount of the nonionic emulsifier is preferably 0.02-0.04 part by weight, such as 0.02, 0.025, 0.03, 0.035, 0.04 part by weight or any value therebetween; the amount of the co-emulsifier is preferably 0.03-0.06 part by weight, such as 0.03, 0.04, 0.05, 0.06 part by weight or any value therebetween.

[0030] Furthermore, the conditions of the modification reaction preferably include: a temperature of 150-180°C, such as 150°C, 160°C, 170°C, 180°C or any value therebetween; and a time of 6-10h, such as 6h, 7h, 8h, 9h, 10h or any value therebetween.

[0031] In a specific embodiment, the preparation steps of the modified wax emulsion are as follows: add the unmodified wax emulsion into a shear emulsifier, disperse it at a rotation speed of 500-800 rpm for 5-10 minutes, then add a non-ionic emulsifier and an auxiliary emulsifier, raise the temperature to 150-180°C at a rotation speed of 1500-3000 rpm, react for 6-10 hours, reduce the rotation speed, and obtain the modified wax emulsion after cooling to room temperature.

[0032] In the present invention, specific examples of the unmodified wax emulsion include, but are not limited to: at least one of polyolefin wax emulsion, carnauba wax emulsion, and silica wax emulsion, more preferably polyethylene wax emulsion and / or polypropylene wax emulsion.

[0033] In the present invention, the nonionic emulsifier is preferably selected from at least one of sorbitan fatty acid ester emulsifiers (Span), polyoxyethylene sorbitan fatty acid ester emulsifiers (Tween), and fatty alcohol polyoxyethylene ether emulsifiers, and specific examples thereof include but are not limited to at least one of Span 20, Span 40, Span 60, Span 65, Span 80, Span 85, Tween 20, Tween 40, Tween 60, Tween 80, and Tween 85. The use of a nonionic emulsifier to modify the wax emulsion is not only conducive to improving the storage stability of the coating system, but also can improve the recoating performance of the coating, and make the modified wax emulsion cooperate with the self-crosslinking emulsion and the silane coupling agent to further improve the adhesion, scratch resistance, and stain resistance of the coating.

[0034] In the present invention, specific examples of the auxiliary emulsifier include, but are not limited to: at least one of polyglycerol ester, glycerol, and stearic acid.

[0035] In the present invention, the self-crosslinking emulsion is preferably an acrylic self-crosslinking emulsion. The particle size of the self-crosslinking emulsion is preferably 0.05 to 0.1 μm, such as 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm, 0.1 μm or any value therebetween. The particle size of the modified wax emulsion is preferably 0.1 to 1 μm, such as 0.1 μm, 0.2 μm, 0.5 μm, 0.8 μm, 1 μm or any value therebetween. At this time, the self-crosslinking emulsion particles with a specific particle size cooperate with the modified wax emulsion particles to further improve the scratch resistance and recoating performance of the coating film.

[0036] In the present invention, the silane coupling agent is preferably at least one selected from aminosilane, epoxysilane, mercaptosilane, alkenylsilane and isocyanatesilane.

[0037] Furthermore, the silane coupling agent is preferably aminosilane and epoxysilane. The mass ratio of aminosilane to epoxysilane is preferably 1:(1-3), such as 1:1, 1:1.5, 1:2, 1:2.5, 1:3 or any value therebetween. This is more conducive to further improving the hydrophobicity, adhesion and density of the coating, and improving the stain resistance and scratch resistance.

[0038] Further, the specific examples of the aminosilane include, but are not limited to, at least one of γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, γ-aminopropyl methyl diethoxysilane, γ-aminopropyl methyl dimethoxysilane, 3-(2-aminoethyl) aminopropyl trimethoxysilane, 3-(2-aminoethyl) aminopropyl triethoxysilane, and 3-(2-aminoethyl) aminopropyl methyl dimethoxysilane. Specific examples of the epoxysilane include, but are not limited to, at least one of γ-glycidyloxypropyl trimethoxysilane, γ-glycidyloxypropyl triethoxysilane, γ-glycidyloxypropyl methyl dimethoxysilane, γ-glycidyloxypropyl methyl diethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane.

[0039] In the present invention, specific examples of the cellulose include, but are not limited to, at least one of carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose.

[0040] In the present invention, specific examples of the inorganic filler include, but are not limited to, at least one of heavy calcium carbonate, barium sulfate, kaolin, talc, diatomaceous earth, mica powder, and calcium silicate powder.

[0041] In the present invention, specific examples of the film-forming aid include, but are not limited to, at least one of alcohol ester dodecahydrate, alcohol ester hexahydrate, OE300, and OE400.

[0042] In the present invention, specific examples of the auxiliary agent include, but are not limited to: at least one of a defoaming agent, a dispersant, a wetting agent, a preservative, a thickener, and an anti-mildew and anti-algae agent.

[0043] Furthermore, based on the total weight of the self-cleaning tile coating, the content of the defoaming agent is preferably 0.2-0.8wt%, such as 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt% or any value therebetween; the content of the dispersant is preferably 0.3-1.0wt%, such as 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1.0wt% or any value therebetween; the content of the wetting agent is preferably 0.1-1.0wt%, such as 0.1wt%, 0.2wt%, 0.5wt%, 0.6wt%, 0.8 wt%, 1.0wt% or any value therebetween; the content of the preservative is preferably 0.1-1.0wt%, such as 0.1wt%, 0.2wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1.0wt% or any value therebetween; the content of the thickener is preferably 0.1-0.8wt%, such as 0.1wt%, 0.2wt%, 0.5wt%, 0.6wt%, 0.8wt% or any value therebetween; the content of the mildew and algae preventer is preferably 0.2-1.0wt%, such as 0.2wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1.0wt% or any value therebetween.

[0044] In the present invention, the defoamer is preferably at least one selected from silicone defoamers, polyether defoamers, polyurethane defoamers, and mineral oil defoamers.

[0045] In the present invention, the dispersant is preferably at least one selected from amine compounds, phosphate compounds, carboxylate compounds, polyacid homopolymer compounds, and polyacid copolymers.

[0046] In the present invention, the wetting agent is preferably at least one of polyoxyethylene ether compounds, polyoxyethylene ester compounds, polyoxyethylene amine compounds and polyoxyethylene siloxane compounds.

[0047] In the present invention, specific examples of the preservative include, but are not limited to, at least one of MIT (methylisothiazolinone), CIT (methylchloroisothiazolinone), and BIT (1,2-benzisothiazolin-3-one).

[0048] In the present invention, specific examples of the thickener include, but are not limited to: at least one of a polyurethane thickener, an alkali swelling thickener, and a bentonite thickener.

[0049] In the present invention, specific examples of the mildew and algae preventer include, but are not limited to: at least one of OIT (2-octyl-4-isothiazoline-3-one), DCOIT (4,5-dichloro-N-octyl-4-isothiazoline-3-one), MIT (2-methyl-4-isothiazoline-3-one), IPBC (3-iodo-2-propargyl butylcarbamate), and ZnP.

[0050] The preparation method of the self-cleaning tile coating provided by the present invention comprises: mixing water, cellulose, pH multifunctional additive, titanium dioxide, inorganic filler, self-crosslinking emulsion, modified wax emulsion, film-forming aid, silane coupling agent and additives to obtain the self-cleaning tile coating. The mixing order of the water, cellulose, pH multifunctional additive, titanium dioxide, inorganic filler, self-crosslinking emulsion, modified wax emulsion, film-forming aid, silane coupling agent and additives is not specifically limited, and they can be added and mixed at the same time, or several of the raw materials can be mixed first and then the remaining raw materials are added and mixed continuously.

[0051] In a specific embodiment, the preparation method comprises the following steps: firstly stirring and mixing cellulose and water until the cellulose is completely swollen, the stirring time t1 can be 10 to 20 min, such as 10 min, 12 min, 15 min, 18 min, 20 min or any value therebetween, then adding pH multifunctional additive and additive and continuing stirring and mixing, the stirring time t2 can be 5 to 15 min, such as 5 min, 8 min, 10 min, 12 min, 15 min or any value therebetween, then adding titanium dioxide and inorganic filler and continuing stirring and mixing, the stirring time t3 can be 15 to 25 min, such as 15 min, 18 min, 20 min, 22 min, 25 min or any value therebetween, finally adding self-crosslinking emulsion, modified wax emulsion, film-forming additive, silane coupling agent and additive and continuing stirring and mixing, the stirring time t4 can be 5 to 15 min, such as 5 min, 8 min, 10 min, 12 min, 15 min or any value therebetween, and the resulting mixture is a self-cleaning tile coating.

[0052] In a specific embodiment, the preparation method comprises the following steps: firstly, stirring and mixing cellulose and water until the cellulose is completely swollen, and the stirring time t1 can be 10 to 20 minutes, such as 10 minutes, 12 minutes, 15 minutes, 18 minutes, 20 minutes or any value therebetween; then, adding a pH multifunctional auxiliary agent, a defoaming agent, a dispersant, a wetting agent, and a preservative, and continuing to stir and mix; and the stirring time t2 can be 5 to 15 minutes, such as 5 minutes, 8 minutes, 10 minutes, 12 minutes, 15 minutes or any value therebetween; Then add titanium dioxide and inorganic filler and continue to stir and mix. The stirring time t3 can be 15 to 25 minutes, such as 15 minutes, 18 minutes, 20 minutes, 22 minutes, 25 minutes or any value therebetween. Finally, add self-crosslinking emulsion, modified wax emulsion, film-forming aid, silane coupling agent, thickener and mildew and algae inhibitor and continue to stir and mix. The stirring time t4 can be 5 to 15 minutes, such as 5 minutes, 8 minutes, 10 minutes, 12 minutes, 15 minutes or any value therebetween. The resulting mixture is a self-cleaning tile coating.

[0053] The present invention will be described in detail below by specific examples. The examples of the embodiments are intended to explain the present invention and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0054] Preparation Example 1 Preparation of modified wax emulsion A1

[0055] Unmodified wax emulsion (oxidized polyolefin wax emulsion, purchased from Jiangsu Tianwen New Material Technology Co., Ltd., brand TW-F0001R), non-ionic emulsifier I (including Span 60 and Tween 80 in a mass ratio of 1:1), and co-emulsifier polyglycerol fatty acid ester (purchased from Beijing Baoguan Additive Co., Ltd.) were weighed in a mass ratio of 1:0.03:0.04.

[0056] The unmodified oxidized polyolefin wax emulsion TW-F0001R was added to a shear emulsifier and dispersed at a speed of 700 rpm for 10 minutes. Then, a non-ionic emulsifier (including Span 60 and Tween 80 in a mass ratio of 1:1) and polyglycerol fatty acid ester were added, the speed was increased to 2000 rpm and the temperature was raised to 165°C. After reacting for 8 hours, the speed was reduced to 500 rpm and the stirring was stopped after the temperature dropped to room temperature to obtain a modified polyethylene wax emulsion A1 with a particle size of 0.4 to 0.6 μm.

[0057] Preparation Example 2 Preparation of modified wax emulsion A2

[0058] Unmodified wax emulsion (oxidized polyolefin wax emulsion, purchased from Jiangsu Tianwen New Material Technology Co., Ltd., brand TW-F0001R), non-ionic emulsifier I (Span 80), and co-emulsifier polyglycerol fatty acid ester (purchased from Beijing Baoguan Additive Co., Ltd.) were weighed in a mass ratio of 1:0.02:0.03.

[0059] The unmodified oxidized polyolefin wax emulsion TW-F0001R was added to a shear emulsifier and dispersed at a speed of 500 rpm for 10 minutes. Then, a nonionic emulsifier (Span 80) and stearic acid were added, the speed was increased to 1500 rpm and the temperature was raised to 150°C. After reacting for 10 hours, the speed was reduced to 500 rpm and stirring was stopped after the temperature dropped to room temperature to obtain a modified polyethylene wax emulsion A2 with a particle size of 0.1-0.3 μm.

[0060] Preparation Example 3 Preparation of modified wax emulsion A3

[0061] Unmodified wax emulsion (polypropylene wax emulsion, purchased from Jiangdong Xinghong Chemical Materials Co., Ltd., brand P640), non-ionic emulsifier I (Tween 60), and co-emulsifier polyglycerol fatty acid ester (purchased from Beijing Baoguan Additive Co., Ltd.) were weighed in a mass ratio of 1:0.04:0.06.

[0062] Unmodified polypropylene wax emulsion P640 was added to a shear emulsifier and dispersed at a speed of 800 rpm for 10 minutes. Then, a nonionic emulsifier (Tween 60) and polyglycerol fatty acid ester were added, the speed was increased to 3000 rpm and the temperature was raised to 180°C. After reacting for 6 hours, the speed was reduced to 500 rpm and stirring was stopped after the temperature dropped to room temperature to obtain modified wax emulsion A3 with a particle size of 0.8 to 1 μm.

[0063] Comparative Preparation Example 1 Preparation of Reference Modified Wax Emulsion DA1

[0064] A reference modified wax emulsion DA1 was prepared according to the method of Preparation Example 1, except that the same mass of hexadecyltrimethylammonium chloride (cationic emulsifier) ​​was used instead of the non-ionic emulsifier (including Span 60 and Tween 80 in a mass ratio of 1:1), and the other conditions were the same as those in Preparation Example 1, thereby preparing a reference modified wax emulsion DA1.

[0065] Comparative Preparation Example 2 Preparation of Reference Modified Wax Emulsion DA2

[0066] A reference modified wax emulsion DA2 was prepared according to the method of Preparation Example 1, except that the same mass of sodium dodecylbenzenesulfonate (anionic emulsifier) ​​was used instead of the non-ionic emulsifier (including Span 60 and Tween 80 in a mass ratio of 1:1), and the other conditions were the same as those in Preparation Example 1, thereby preparing a reference modified wax emulsion DA2.

[0067] Example 1 Preparation of self-cleaning tile coating

[0068] The raw materials include: 22.0wt% of deionized water, 0.4wt% of cellulose, 0.1wt% of pH multifunctional additive, 0.2wt% of defoaming agent, 0.6wt% of dispersant, 0.1wt% of wetting agent, 0.2wt% of preservative, 10.0wt% of titanium dioxide, 5.0wt% of inorganic filler, 50.0wt% of self-crosslinking emulsion, 5.0wt% of modified polyethylene wax emulsion A1, 3.8wt% of film-forming additive, 0.2wt% of thickener, 2.0wt% of silane coupling agent, and 0.4wt% of mildew and algae preventer. Among them, cellulose is methyl cellulose; the pH multifunctional additive is specifically 2-amino-2-methyl-1-propanol, purchased from Angus Company with the brand name AMP-95; the defoamer is Blackburn's CF1829 silicone defoamer; the dispersant is Nouryon Chemical's Alcosperse747 hydrophobically modified copolymer dispersant; the wetting agent is Nouryon's Ethylan1005 wetting agent; the preservative is MIT; the inorganic filler is heavy calcium carbonate; the film-forming aid is alcohol ester twelve; the thickener is Dow Chemical's RM-8W polyurethane thickener; the silane coupling agent includes γ-aminopropyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane in a mass ratio of 1:1.5; the mildew and algae inhibitor is OIT; the self-crosslinking emulsion is an acrylic self-crosslinking emulsion purchased from Wanhua Chemical Company with the brand name 8218, particle size is 0.05-0.1μm.

[0069] Preparation steps: first stir and mix cellulose with water until the cellulose is completely swollen, the stirring time t1 is 15 minutes, then add pH multifunctional additive, defoaming agent, dispersant, wetting agent, preservative and continue to stir and mix, the stirring time t2 is 10 minutes, then add titanium dioxide and inorganic filler and continue to stir and mix, the stirring time t3 can be 20 minutes, finally add self-cross-linking emulsion, modified wax emulsion, film-forming aid, silane coupling agent, thickener, mildew and algae inhibitor and continue to stir and mix, the stirring time t4 is 10 minutes, and the resulting mixture is the self-cleaning tile coating.

[0070] Example 2 Preparation of self-cleaning tile coating

[0071] The raw materials include: 17.0wt% of deionized water, 0.4wt% of cellulose, 0.1wt% of pH multifunctional additive, 0.2wt% of defoaming agent, 0.6wt% of dispersant, 0.1wt% of wetting agent, 0.2wt% of preservative, 8.0wt% of titanium dioxide, 3.0wt% of inorganic filler, 60.0wt% of self-crosslinking emulsion, 3.0wt% of modified polyethylene wax emulsion A2, 2.8wt% of film-forming additive, 0.2wt% of thickener, 4.0wt% of silane coupling agent, and 0.4wt% of mildew and algae preventer. Among them, cellulose is carboxymethyl cellulose; the pH multifunctional additive is specifically 2-amino-2-methyl-1-propanol, purchased from Angus Company with the brand name AMP-95; the defoamer is Blackburn's CF1829 silicone defoamer; the dispersant is Nouryon Chemical's Alcosperse797 hydrophobic dispersant; the wetting agent is Nouryon's Ethylan324 wetting agent; the preservative is CIT; the inorganic filler is talc; the film-forming aid is OE300; the thickener is Dow Chemical's RM-2020NPR polyurethane thickener; the silane coupling agent includes γ-aminopropylmethyldimethoxysilane and γ-glycidyloxypropyltriethoxysilane in a mass ratio of 1:1; the mildew and algae inhibitor is DCOIT; the self-crosslinking emulsion is an acrylic self-crosslinking emulsion purchased from Wanhua Chemical Company with the brand name 8218, particle size is 0.05-0.1μm.

[0072] Preparation steps: The same as the preparation method in Example 1, thus preparing a self-cleaning tile coating.

[0073] Example 3 Preparation of self-cleaning tile coating

[0074] The raw materials include: 22.0wt% of deionized water, 0.4wt% of cellulose, 0.1wt% of pH multifunctional additive, 0.2wt% of defoaming agent, 0.6wt% of dispersant, 0.1wt% of wetting agent, 0.2wt% of preservative, 15.0wt% of titanium dioxide, 8.0wt% of inorganic filler, 40.0wt% of self-crosslinking emulsion, 8.0wt% of modified polyethylene wax emulsion A3, 3.8wt% of film-forming additive, 0.2wt% of thickener, 1.0wt% of silane coupling agent, and 0.4wt% of mildew and algae preventer. Among them, cellulose is hydroxyethyl cellulose; the pH multifunctional additive is specifically 2-amino-2-methyl-1-propanol, purchased from Angus Company with the brand name AMP-95; the defoamer is Blackburn's CF1829 silicone defoamer; the dispersant is Nouryon Chemical's Alcosperse755 acrylate copolymer dispersant; the wetting agent is Nouryon's Ethylan1008 wetting agent; the preservative is BIT; the inorganic filler is diatomaceous earth; the film-forming aid is alcohol ester hexadecene; the thickener is Dow Chemical's RM-12W polyurethane thickener; the silane coupling agent includes 3-(2-aminoethyl)aminopropyltrimethoxysilane and γ-glycidyloxypropylmethyldimethoxysilane in a mass ratio of 1:3; the mildew and algae inhibitor is IPBC; the self-crosslinking emulsion is an acrylic self-crosslinking emulsion purchased from Wanhua Chemical Company with the brand name 8218, particle size is 0.05-0.1μm.

[0075] Preparation steps: The same as the preparation method in Example 1, thus preparing a self-cleaning tile coating.

[0076] Example 4 Preparation of self-cleaning tile coating

[0077] The raw materials include: the same as Example 1, except that the silane coupling agent only includes γ-aminopropyltriethoxysilane.

[0078] Preparation steps: The same as the preparation method in Example 1, thus preparing a self-cleaning tile coating.

[0079] Example 5 Preparation of self-cleaning tile coating

[0080] The raw materials include: the same as Example 1, except that the silane coupling agent only includes γ-glycidyloxypropyltrimethoxysilane.

[0081] Preparation steps: The same as the preparation method in Example 1, thus preparing a self-cleaning tile coating.

[0082] Comparative Example 1 Preparation of Reference Self-Cleaning Tile Coating

[0083] The raw materials include: 22wt% deionized water, 0.4wt% methyl cellulose, 0.1wt% pH multifunctional additive (2-amino-2-methyl-1-propanol), 0.2wt% CF1829 silicone defoamer, 0.6wt% Alcosperse747 hydrophobically modified copolymer dispersant, 0.1wt% Nouryon Ethylan1005 wetting agent, and preservative MIT 0.2wt%, titanium dioxide 10.0wt%, inorganic filler (heavy calcium carbonate) 5.0wt%, non-self-crosslinking emulsion (purchased from Badfu Group Co., Ltd., brand RS-2806) 50.0wt%, modified polyethylene wax emulsion A15.0wt%, film-forming aid alcohol ester twelve 3.8wt%, RM-8W polyurethane thickener 0.2wt%, silane coupling agent mass ratio of 1:1.5 γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane 2.0wt%, mildew and algae inhibitor OIT 0.4wt%.

[0084] Preparation steps: The same as the preparation method in Example 1, thus preparing a reference self-cleaning tile coating.

[0085] Comparative Example 2 Preparation of Reference Self-Cleaning Tile Coating

[0086] The raw materials include: deionized water 22.0wt%, methyl cellulose 0.4wt%, pH multifunctional additive (2-amino-2-methyl-1-propanol) 0.1wt%, CF1829 silicone defoamer 0.2wt%, Alcosperse747 hydrophobically modified copolymer dispersant 0.6wt%, Nouryon Ethylan1005 wetting agent 0.1wt%, preservative MIT 0.2wt%, titanium dioxide 10.0wt%, inorganic filler (heavy calcium carbonate) 5.0wt%, self-crosslinking emulsion (acrylic self-crosslinking emulsion, purchased from Wanhua Chemical Company, brand 8218) 50.0wt%, unmodified oxidized polyolefin wax emulsion TW-F0001R 5.0wt%, film-forming aid alcohol ester dodecahydrate 3.8wt%, RM-8W polyurethane thickener 0.2wt%, silane coupling agent gamma-aminopropyl triethoxysilane and gamma-glycidyl ether oxypropyl trimethoxysilane in a mass ratio of 1:1.5 2.0wt%, mildew and algae preventer OIT 0.4wt%.

[0087] Preparation steps: The same as the preparation method in Example 1, thus preparing a reference self-cleaning tile coating.

[0088] Comparative Example 3 Preparation of Reference Self-Cleaning Tile Coating

[0089] The raw materials include: the same as those in Comparative Example 1, except that the reference modified wax emulsion DA1 of the same mass is used instead of the modified polyethylene wax emulsion A1.

[0090] Preparation steps: The same as the preparation method in Example 1, thus preparing a reference self-cleaning tile coating.

[0091] Comparative Example 4 Preparation of Reference Self-Cleaning Tile Coating

[0092] The raw materials include: the same as those in comparative example 1, except that the reference modified wax emulsion DA2 of the same mass is used instead of the modified polyethylene wax emulsion A1.

[0093] Preparation steps: The same as the preparation method in Example 1, thus preparing a reference self-cleaning tile coating.

[0094] Test Case

[0095] The properties of the self-cleaning tile coatings prepared in the above examples and comparative examples were tested according to the following method, and the results are shown in Tables 1 and 2.

[0096] (1) The alkali resistance, water resistance and initial drying crack resistance of the coating were tested according to the method in JG / T 24-2018 "Synthetic resin emulsion sand-walled architectural coatings". The wash resistance of the coating was tested according to the method in GB / T 9266-2009 "Determination of wash resistance of architectural coatings".

[0097] (2) Viscosity change after 15 days of hot storage: refer to the method in JG / T 24-2018 "Synthetic resin emulsion sand-walled architectural coatings". Put the coating into glass or plastic, seal it, and place it in a constant temperature box at (50±2)℃ for 15 days. Take it out and record the viscosity before and after hot storage.

[0098] (3) Scratch resistance test: According to the method in GB / T 6739-2022 "Determination of film hardness of paints and varnishes by pencil method", the hardness of different coatings was tested and scored based on the results. The score ranged from 1 to 5. The worse the scratch resistance, the lower the score.

[0099] (4) Recoatability test: The test sample is coated on black and white contrast test cardboard with a 100 μm wire rod. After drying for 24 hours, the test sample is coated again on the surface of the coating that has been dried for 24 hours with a 100 μm wire rod. The coating is observed for bubbling, fish eyes, pinholes, etc. after drying. The coating is scored and graded on a scale of 1-5. The worse the recoatability, the lower the score.

[0100] (5) Anti-fouling test: The test was conducted in accordance with method 5.4 of GB / T 9780-2013 "Test method for anti-fouling of architectural coatings". The anti-fouling property was evaluated by the decrease rate X (%) of the reflectance coefficient of the coating. The larger the X value, the worse the anti-fouling property.

[0101] (6) Adhesion test: The adhesion performance of the coating is tested according to the method in GB / T 9286-2021 "Scratch test for paints and varnishes". The test results are graded from 0 to 5, with grade 0 being the best adhesion and grade 5 being the worst adhesion.

[0102] Table 1

[0103]

[0104] Table 2

[0105]

[0106]

[0107] It can be seen from the results in Table 1 that, compared with Comparative Examples 1 to 4, the self-cleaning tile coatings provided by Examples 1 to 5 of the present invention have better hydrophobicity, stain resistance, recoating performance, good adhesion and scratch resistance, and good thermal storage performance.

[0108] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A self-cleaning tile coating, characterized in that: Based on the total weight of the self-cleaning tile coating, the self-cleaning tile coating contains 8.0-30.0wt% of water, 0.1-0.6wt% of cellulose, 0.1-1.0wt% of pH multifunctional additive, 5.0-20.0wt% of titanium dioxide, 3.0-10.0wt% of inorganic filler, 30.0-60.0wt% of self-crosslinking emulsion, 1.0-10.0wt% of modified wax emulsion, 2.0-6.0wt% of film-forming additive, 1.0-5.0wt% of silane coupling agent and 0.1-5.6wt% of additive; the modified wax emulsion is obtained by modifying an unmodified wax emulsion with a non-ionic emulsifier and an auxiliary emulsifier.

2. The self-cleaning tile coating according to claim 1, characterized in that: The mass ratio of the unmodified wax emulsion to the nonionic emulsifier and the co-emulsifier is 1:(0.02-0.04):(0.03-0.06).

3. The self-cleaning tile coating according to claim 1, characterized in that: The unmodified wax emulsion is selected from at least one of polyethylene wax emulsion, carnauba wax emulsion, silica wax emulsion and polypropylene wax emulsion; Preferably, the nonionic emulsifier is selected from at least one of sorbitan fatty acid ester emulsifiers, polyoxyethylene sorbitan fatty acid ester emulsifiers, and fatty alcohol polyoxyethylene ether emulsifiers; Preferably, the auxiliary emulsifier is selected from at least one of polyglycerol esters, glycerol and stearic acid.

4. The self-cleaning tile coating according to claim 1, characterized in that: The modification reaction conditions include: temperature of 150-180° C. and time of 6-10 hours.

5. The self-cleaning tile coating according to claim 1, characterized in that: The particle size of the modified wax emulsion is 0.1 to 1 μm; Preferably, the particle size of the self-crosslinking emulsion is 0.05 to 0.1 μm; Preferably, the self-crosslinking emulsion is an acrylic self-crosslinking emulsion.

6. The self-cleaning tile coating according to claim 1, characterized in that: The silane coupling agent is selected from aminosilane and epoxysilane; Preferably, the mass ratio of the aminosilane to the epoxysilane is 1:(1-3).

7. The self-cleaning tile coating according to claim 1, characterized in that: The cellulose is selected from at least one of carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose; Preferably, the inorganic filler is selected from at least one of heavy calcium carbonate, barium sulfate, kaolin, talc, diatomaceous earth, mica powder, and calcium silicate powder; Preferably, the film-forming aid is selected from at least one of alcohol ester dodecahydrate, alcohol ester hexadecene, OE300, and OE400; Preferably, the auxiliary agent is selected from at least one of a defoaming agent, a dispersant, a wetting agent, a preservative, a thickener, and an anti-mildew and anti-algae agent.

8. The self-cleaning tile coating according to claim 7, characterized in that: Based on the total weight of the self-cleaning tile coating, the content of the defoamer is 0.2-0.8wt%, the content of the dispersant is 0.3-1.0wt%, the content of the wetting agent is 0.1-1.0wt%, the content of the preservative is 0.1-1.0wt%, the content of the thickener is 0.1-0.8wt%, and the content of the mildew and algae preventer is 0.2-1.0wt%.

9. The method for preparing the self-cleaning tile coating according to any one of claims 1 to 8, characterized in that: The preparation method of the self-cleaning tile coating comprises: mixing water, cellulose, pH multifunctional additive, titanium dioxide, inorganic filler, self-crosslinking emulsion, modified wax emulsion, film-forming additive, silane coupling agent and additives to obtain the self-cleaning tile coating.

10. Use of the self-cleaning tile coating according to any one of claims 1 to 8 in kitchen and bathroom tiles and other building materials.